Ganong's Review of Medical Physiology - Barrett, Kim E. et.al (New Delhi Tata McGraw Hill Education Private Ltd., 2010)
One of the world's leading texts on medical physiology, 'Ganong's Review of Medical Physiology' has been redesigned with a new full-colour format and expanded pedagogical features. Examples from clinical medicine are integrated the chapters to illustrate important physiologic concepts.
Include Index
Keywords: Physiology -- Human physiology